Elective Management of the Neck in Parotid Tumours. Issue 12 (December 2018) - Ng-Cheng-Hin, B.; Glaholm, J.; Awad, Z.; Gujral, D.M.
Abstract: Aims: Management of the clinically node-negative (cN0) neck for parotid tumours remains controversial. Options include observation, elective neck dissection (END) or elective nodal irradiation (ENI). We reviewed the evidence for ENI on a background of current practice among UK clinical oncologists. Materials and methods: We carried out a systematic search of PubMed between 1 January 1980 and 31 December 2016. Articles on patients treated with parotidectomy and either END or ENI, and studies on nodal patterns of disease, were included. UK clinical oncologists were asked to complete an online questionnaire regarding their use of neck radiotherapy in this setting. Results: From 96 references, 20 studies met the inclusion criteria: 11 reported on END, five on ENI and two on both. Eight studies reported on nodal patterns of disease. The prevalence of occult nodal metastases after END ranged from 0 to 45%. Five year locoregional control was variable (range 64–100%). For ENI, 5 year locoregional control varied from 74 to 100%. High-grade and T3/T4 tumours were factors for nodal relapse after END or ENI, which most commonly occurred in levels I–III. For the survey, 33/50 (66%) of cancer centres responded. Fourteen (42%) centres had guidelines for ENI. Most centres considered high-grade tumours (96%), T3/T4 disease (80%) and lymphovascular invasion (88%) as indications for ENI. Twelve centres (36%) irradiated levels Ib–IV electively; the remaining centres treated other various combinations of nodal levels. Conclusion: There is heterogeneity in the use and indications for ENI in the UK. ENI is a reasonable alternative to END as elective management for the cN0 neck in patients with high-grade tumours or T3/T4 disease. The elective clinical target volume should at least encompass nodal levels I–III. Highlights: Management of the clinically node negative neck in parotid tumours is controversial. Options are observation, elective neck dissection (END) or nodal irradiation (ENI). A lack of consensus in indications and use of ENI amongst UK oncologists exists. Published data on over 1000 patients support ENI as an alternative to END.